PENGEMBANGAN METODE HPTLC-SPEKTROFOTODENSITOMETRI UNTUK PEMISAHAN SENYAWA RIFAMPISIN, ISONIAZID, PIRAZINAMIDA, DAN ETAMBUTOL - Prawiranata, I Putu Hengky; Sugiastana, Bagus Nyoman; Putra, I Putu Krisnantara Wijaya; Dharmapradnyawati, Ni Nyoman Putri; Widhiartini, Ida Ayu Alit; Wirasuta, I Made Agus Gelgel; Widjaja, I Nyoman Kadjeng (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
A simple chromatography saparation method for rifampicin, isoniazid, pyrazinamide, and ethambutol by using an impregnated TLC plate with paraffin has been studied. The aim of this study was to develop as simultan separation method of rifampicin, isoniazid, pyrazinamide, and ethambutol. TLC silica gel GF254 was impregnated with paraffin in diethyl ether 10% (v/v). Plate was actived on 110°C, 30 minutes. Some variation of mobile phase was used based on a mixture of ethanol and water. The best chromatographic parameters resulting in use a mixture of ethanol:water (95:5 v/v) were added 5% of glacial acetic acid and 1% of diethylamine as mobile phase. Ethambutol can was derivatized by iodine vapor, but it not detected at a TLC-spektrofotodensitometer, so for a validation only rifampicin, isoniazid, and pyrazinamide. This mobile phase gave good separation with Rs>1 and α>1. The chromatography plates were scanned at 335 nm for rifampicin and at 275 nm for isoniazid and pyrazinamide using a TLC-spektrofotodensitometer. Method validation was includes determining the specificity, LOD, and precision of the method. The method was developed in this study had good validation. Specificity of method was determined by purity factor value, on this method was obtained of purity factor (r(s,m) dan r(m,e))<0,99. The results of this study indicate good precision by intraday and interday assay (RSD<20%) of the method validation. LOD for rifampicin, isoniazid, and pyrazinamide was 15,339 ng, 29,719 ng, and 26,892 ng respectively. The method was developed can be used as a reference for separation of rifampicin, isoniazid, pyrazinamide, and ethambutol in biologis or drug samples. Keywords: Rifampicin, isoniazid, pyrazinamide, ethambutol, impregnation, derivatization